2011
DOI: 10.1007/s11104-011-0959-8
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced nodulation and symbiotic effectiveness of Medicago truncatula when co-inoculated with Pseudomonas fluorescens WSM3457 and Ensifer (Sinorhizobium) medicae WSM419

Abstract: Aims Low numbers of rhizobia in soil or inoculants delay nodulation and decrease symbiotic legume productivity. This study investigated the effect of coinoculation with a helper bacterium, Pseudomonas fluorescens WSM3457 on the Medicago truncatulaEnsifer (Sinorhizobium ) medicae WSM419 symbiosis challenged by a low inoculum dose. Methods In a glasshouse experiment the effect of coinoculation with WSM3457 on the kinetics of nodule initiation and development was assessed 5, 7, 10, 14, 17, 21, and 42 days after i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 52 publications
0
41
2
Order By: Relevance
“…Previous studies have reported positive effects of dual inoculation with IAA‐producing bacteria and rhizobia on leguminous crops nodulation. However, these studies do not necessary reflect the direct involvement of auxin in interactions between IAA‐producing bacteria and nodulation as these bacteria show siderophore production and phosphate solubilization activity simultaneously (Fox, O'Hara, & Bräu, ; Malik & Sindhu, ; Srinivasan, Holl, & Petersen, ). Herein, our experiments demonstrate that auxin is involved in the enhancement of rhizobial symbiosis by the mutualistic fungus P. liquidambari through transcriptional activation of nodulation signalling pathway and promotion of nodule carbon metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported positive effects of dual inoculation with IAA‐producing bacteria and rhizobia on leguminous crops nodulation. However, these studies do not necessary reflect the direct involvement of auxin in interactions between IAA‐producing bacteria and nodulation as these bacteria show siderophore production and phosphate solubilization activity simultaneously (Fox, O'Hara, & Bräu, ; Malik & Sindhu, ; Srinivasan, Holl, & Petersen, ). Herein, our experiments demonstrate that auxin is involved in the enhancement of rhizobial symbiosis by the mutualistic fungus P. liquidambari through transcriptional activation of nodulation signalling pathway and promotion of nodule carbon metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Some of them belonged to wellknown plant growth-promoting genera, such as Pseudomonas (Kloepper et al 1989), Kosakonia (Peng et al 2009), Rhizobium (Bertrand et al 2007, and Ensifer (Fox et al 2011). Previously, Collavino et al (2010) isolated phosphate-solubilizing bacterial strains from the roots and rhizosphere of yerba mate, which were assigned to the genera Enterobacter, Pantoea, Pseudomonas, Acinetobacter, Burkholderia, and Exiguobacterium.…”
Section: Discussionmentioning
confidence: 99%
“…balustinum Aur9 might have improved rhizobial infection at initial stages by increasing root hair formation and infection sites which in turn might have added to increase the formation of nodule primordia and early nodule development. Similarly, Fox et al ( 2011 ), while reporting enhanced rate of nodule initiation in Medicago truncatula cv. Caliph as a result of co-inoculation of P .…”
Section: Creation Of Additional Infection Sitesmentioning
confidence: 95%
“…Hence, any stimulus that causes increase in root growth could result in more colonization sites for rhizobia (Fox et al 2011 ). It has been recognized that growth and yield of leguminous plants could be enhanced by creating additional infection sites through inoculation of rhizobia in combination with benefi cial rhizosphere bacteria (Plazinski and Rolfe 1985 ;Yahalom et al 1987Yahalom et al , 1990.…”
Section: Creation Of Additional Infection Sitesmentioning
confidence: 99%
See 1 more Smart Citation